Phthiriasis palpebrarum, thelaziasis, and ophthalmomyiasis. (July 2020) - Luo, Ban; Xiang, Nan; Liu, Rong; Wang, Wei; Li, Yunping; Qi, Xin
Highlights: We systematically analyzed several distinct and unique parasite characteristics on ocular surface, especially latency and crypsis We proposed specific examination techniques and methods as well as prevention and treatment strategies from these specific perspectives Our suggestions provide help with prompt timely diagnoses and early interventions for these diseases by health care workers and improve the public's awareness of parasitic infections. Abstract: Introduction: Parasitic infections of the eye are a major cause of ocular-surface diseases globally. While most infections are treatable, parasites can cause varying levels of damage mostly due to late diagnosis or misdiagnosis as a result of doctors' unfamiliarity with their characteristics of latency and crypsis, as well as lack of awareness by the patients. Case Reports: In this study, we present three cases of phthiriasis palpebrarum, thelaziasis, and ophthalmomyiasis, respectively. Two of the cases were treated at the clinic and did not recur. One patient refused treatment and was lost to follow-up. Discussion: By evaluating the natural histories, morphology, symptoms, clinical findings, and treatment of these parasitic diseases, we systematically analyzed several distinct and unique parasite characteristics, especially latency and crypsis. Furthermore, we have proposed specific examination techniques and methods as well as prevention and treatment strategies from these specific perspectives, aiming to prompt timely diagnoses and early interventions for these diseases by health care workers and improve the public's awareness of parasitic infections. Conclusion: Parasitosis on the ocular surface is a global infectious disease, and prevention strategies include maintaining personal and environmental hygiene and limiting contact with animals. We recommend that health care workers should enhance their ability to detect and diagnose these diseases while promoting the public's awareness of them in the context of our new perspectives.